Biodiversity, Societies, and States: cooperation lessons in transboundary protected areas - Kropf, Marcela Stüker; Ferro, Silvia Lilian; Oliveira, Rogério Ribeiro (Sociedade & Natureza, 2019)
Border protected areas are important tools of nature conservation, and emblematic of the relations between society and nature. These areas enable cooperative processes and political, social, and cultural integration of the territory. Europe is pioneer in the creation, integrated management, and certification of border protected areas. Considering the possibility of using these instruments in Brazilian cases of shared management with countries on the frontier, six areas were visited and interviews were conducted with their managers. The research is qualitative, following the methodology of speeches content analysis. The areas indicate the enhancement of regional and local culture. Managers speech revealed practical elements of transboundary cooperation, such as objectives, benefits, and difficulties. The main recommendations for implementing better levels of cooperation are the sustained motivation and mutual understanding among those involved. The research highlight the social importance of the natural heritage, the present and future conservation of the cultural and ecological attributes.